2022
DOI: 10.3389/fnagi.2022.857521
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Conventional Logistic Regression and Machine Learning Methods for Predicting Delayed Cerebral Ischemia After Aneurysmal Subarachnoid Hemorrhage: A Multicentric Observational Cohort Study

Abstract: BackgroundTimely and accurate prediction of delayed cerebral ischemia is critical for improving the prognosis of patients with aneurysmal subarachnoid hemorrhage. Machine learning (ML) algorithms are increasingly regarded as having a higher prediction power than conventional logistic regression (LR). This study aims to construct LR and ML models and compare their prediction power on delayed cerebral ischemia (DCI) after aneurysmal subarachnoid hemorrhage (aSAH).MethodsThis was a multicenter, retrospective, obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 36 publications
1
17
1
Order By: Relevance
“…Hu et al. developed an online prediction tool based on a random forest model to identify patients at a high risk of delayed cerebral ischemia after aSAH 30 . Fang et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hu et al. developed an online prediction tool based on a random forest model to identify patients at a high risk of delayed cerebral ischemia after aSAH 30 . Fang et al.…”
Section: Discussionmentioning
confidence: 99%
“…29 Hu et al developed an online prediction tool based on a random forest model to identify patients at a high risk of delayed cerebral ischemia after aSAH. 30 Fang et al reported that elevated D-dimer levels on admission were associated with short-and long-term mortality. 31 Wi sniewski et al found that glucose-6phosphate dehydrogenase and 8-iso-prostaglandin F2a are potential predictors of delayed cerebral ischemia after aSAH.…”
Section: Discussionmentioning
confidence: 99%
“…153 Supervised ML models using broader EHR and imaging data confirmed known DCI risk factors like SAH volume and initial GCS, though also identified new predictors such as leukocytosis and neutrophilia, indicating a potential neuroinflammatory component in the disease process. 154,155 Similarly, an integrative ML model showed superior predictive power over logistic regression (AUC: 0.74 vs. 0.63) and identified potentially modifiable risk factors like treatment modality and timing from ictus to imaging by employing a Local Interpretable Model-agnostic Explanation (LIME) program that provides clear interpretation of each model prediction decision. 156 Furthermore, ML has also been instrumental in discovering novel biomarkers that could enhance DCI and clinical outcome models and provide insights into the molecular and physiological changes in this complex condition.…”
Section: Subarachnoid Hemorrhagementioning
confidence: 99%
“…Similarly, work including transfer function analysis (TFA), the continuous wavelet transform (CWT), empirical mode decomposition (EMD), fast Fourier transform (FFT), cross-spectral analysis, wavelet analysis, Granger causality, autoregressive (AR) models, and so on [ 9 ] have been described. In addition to the statistical time-series analysis techniques, there are various machine learning algorithms used for cerebral physiologic signal modeling [ 10 , 11 ] as well as for the prediction task [ 12 ], including models such as linear regression, artificial neural networks (ANNs), convolutional neural networks (CNNs), extreme gradient boosting (XGBoost), and decision trees. These algorithms offer adaptability and data-driven capabilities that can uncover intricate patterns within the data, particularly in cases where complexities demand more flexible modeling approaches [ 13 ].…”
Section: Introductionmentioning
confidence: 99%